Penggunaan Doa Batuna'u dalam Tradisi Etnik Lio di Desa Ngalukoja Kecamatan Maurole Kabupaten Ende: Sebuah Kajian Linguistik Kebudayaan - Mboka, Idris (Paradigma: Jurnal Kajian Budaya, 2016)
This study aims to identify and describes the verbal symbols and cultural imagery of Lio Ethnic (LE) community which are contained in Batuna’u Prayer (BP). The theory used as analytical scalpel is the Cultural Linguistics Theory (CLT). This study shows 5 forms of BP used in LE community, which are the traditional house construction BP (THC), going to sow BP (GS), delivering dowry BP (DD), going to school BP (GSC), and deceased person BP (DP). From these five forms of BP, there are verbal symbols of a language grammatical discourse (phonology, morphology, and syntax), and the metaphor styles of language, metonymy, poetic sound, and pararelism phrase. After in-depth interpretation of those verbal symbols, some cultural imagery of LE community has been found, such as (1) belief/religion imagery, (2) social imagery, (3) political imagery, (4) human ego towards else imagery, (5) beauty imagery, (6) fear imagery, (7) appreciative imagery, and (8) honor imagery. These study findings describe the noble values which are manifested in Batuna’u prayers. Therefore, they will be beneficial for the Lio Ethnic community in general, and especially for Lio Ethnic students and scholars that have not recognized the noble values contained in Batuna’u prayers.